A flexible ionic synaptic device and diode-based aqueous ion sensor utilizing asymmetric polyelectrolyte distribution. Issue 59 (10th July 2018) - Zhao, Yiwei; Dai, Shilei; Chu, Yingli; Wu, Xiaohan; Huang, Jia
Abstract : Two terminal ionic synaptic devices and pH sensors based on ionic diodes were developed by utilizing asymmetric polyelectrolyte distribution. Abstract : This work reported the development of an ionic diode of high rectification ratio with a simple device structure and a quick fabrication process by utilizing asymmetric polyelectrolyte distribution. Detection of aqueous ions was demonstrated by applying this diode as a pH sensor. Two terminal ionic synaptic devices utilizing a similar structural design were also successfully developed.